The Economic Imperative: Are AI Clinical Trials Cheaper, or Just Better? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Economic Imperative: Are AI Clinical Trials Cheaper, or Just Better? The development of a new drug is a monumental undertaking, often costing billio...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation